2019
DOI: 10.1186/s13550-019-0575-9
|View full text |Cite
|
Sign up to set email alerts
|

Low septal to lateral wall 18F-FDG ratio is highly associated with mechanical dyssynchrony in non-ischemic CRT candidates

Abstract: BackgroundIn order to better understand the concept of mechanical dyssynchrony, a promising hallmark of cardiac resynchronization therapy (CRT) response, we investigated its effect on regional myocardial metabolism and myocardial blood flow (MBF) in non-ischemic CRT candidates.ResultsThirty consecutive non-ischemic CRT eligible patients underwent static 18F-FDG and resting dynamic 13N-NH3 PET/CT. 18F-FDG uptake and MBF for septal and lateral wall were analysed and septal-to-lateral wall ratios (SLR) were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…We can observe small differences with a slightly decreased value of 61 ml/100g/min in the apical region and a slightly higher value in the lateral wall area of 72 ml/100g/min. These values and small deviations correspond well to standard mean blood flow (MBF) in the literature [40].…”
Section: F Clinical Example Of Myocardial Perfusion Measurementsupporting
confidence: 84%
“…We can observe small differences with a slightly decreased value of 61 ml/100g/min in the apical region and a slightly higher value in the lateral wall area of 72 ml/100g/min. These values and small deviations correspond well to standard mean blood flow (MBF) in the literature [40].…”
Section: F Clinical Example Of Myocardial Perfusion Measurementsupporting
confidence: 84%
“…Correspondingly, several positron emission tomography (PET) studies in patients with LBBB have consistently shown a reduced septal and increased lateral wall metabolism ( 9 11 , 47 ). A linear correlation between regional myocardial work, metabolism, and blood flow in subjects with and without mechanical dyssynchrony was found in a study by Degtiarova et al ( 48 ). Our model predictions of myocardial oxygen demand and supply in LBBB are in line with these observations, demonstrating pronounced heterogeneity in both factors due to coronary flow regulation to varying demand ( Fig.…”
Section: Discussionmentioning
confidence: 73%
“…This concept of detecting viable or scarred tissue with PET might be challenging in patients with ventricular conduction abnormalities. In previous work, we have demonstrated a heterogeneous regional distribution of absolute myocardial perfusion and glucose metabolism in nonischemic CRT candidates [4,5]. In particular, a low 13 N-NH 3 -derived absolute myocardial blood flow (MBF) and 18 F-FDG uptake in the septum were observed with high values in the lateral wall, most likely representing a physiological adaptation of the heart to the alterations in myocardial workload and energy demands [6].…”
Section: Introductionmentioning
confidence: 99%